Pertanggungjawaban Negara terhadap Perlindungan Warisan Budaya dalam Konflik Bersenjata dalam Aspek Hukum Humaniter Internasional - Periani, Aniek; Kusumawardana, Haris; Djatmiko, Agoes (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Armed conflict has caused a lot of loss, damage and destruction of a country's cultural heritage. This writing aims to see and explain what International Humanitarian Law provides protection for cultural heritage in conflict. Even though the protection of cultural objects has been regulated through various international conventions, there are behaviors that cause the destruction of these cultural objects in countries in conflict. To obtain data, library research was carried out by studying and analyzing conventions, books, newspapers, scientific writings and relevant literature both online and offline. Then the analysis is carried out using the content analysis method by focusing on what issues are effective in protecting International Humanitarian Law in protecting cultural heritage in conflict areas. The research results show that cultural objects are the identity and cultural heritage of society, so attacks on these objects often increase the escalation of conflict. Attacks by air bombs, bullets and long-range missiles can damage cultural objects as a result of armed conflict.